Cross‐Ancestry Genome‐Wide Association Study Defines the Extended CYP2D6 Locus as the Principal Genetic Determinant of Endoxifen Plasma Concentrations. Issue 3 (31st January 2023) - Khor, Chiea Chuen; Winter, Stefan; Sutiman, Natalia; Mürdter, Thomas E.; Chen, Sylvia; Lim, Joanne Siok Liu; Li, Zheng; Li, Jingmei; Sim, Kar Seng; Ganchev, Boian; Eccles, Diana; Eccles, Bryony; et al.
Abstract : The therapeutic efficacy of tamoxifen is predominantly mediated by its active metabolites 4‐hydroxy‐tamoxifen and endoxifen, whose formation is catalyzed by the polymorphic cytochrome P450 2D6 (CYP2D6). Yet, known CYP2D6 polymorphisms only partially determine metabolite concentrations in vivo . We performed the first cross‐ancestry genome‐wide association study with well‐characterized patients of European, Middle‐Eastern, and Asian descent ( n = 497) to identify genetic factors impacting active and parent metabolite formation. Genome‐wide significant variants were functionally evaluated in an independent liver cohort ( n = 149) and in silico . Metabolite prediction models were validated in two independent European breast cancer cohorts ( n = 287, n = 189). Within a single 1‐megabase (Mb) region of chromosome 22q13 encompassing the CYP2D6 gene, 589 variants were significantly associated with tamoxifen metabolite concentrations, particularly endoxifen and metabolic ratio (MR) endoxifen/ N ‐desmethyltamoxifen (minimal P = 5.4E−35 and 2.5E−65, respectively). Previously suggested other loci were not confirmed. Functional analyses revealed 66% of associated, mostly intergenic variants to be significantly correlated with hepatic CYP2D6 activity or expression ( ρ = 0.35 to −0.52), and six hotspot regions in the extended 22q13 locus impacting gene regulatory function. Machine learning models based on hotspot variants ( n = 12) plus CYP2D6 activity score (AS) increased the explained variability ( 9%) compared with AS alone, explaining up to 49% (median R 2 ) and 72% of the variability in endoxifen and MR endoxifen/ N ‐desmethyltamoxifen, respectively. Our findings suggest that the extended CYP2D6 locus at 22q13 is the principal genetic determinant of endoxifen plasma concentration. Long‐distance haplotypes connecting CYP2D6 with adjacent regulatory sites and nongenetic factors may account for the unexplained portion of variability.